Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13048-017-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged hypothyroidism severely reduces ovarian follicular reserve in adult rats

Abstract: BackgroundThere is substantial evidence both in humans and in animals that a prolonged reduction in plasma thyroid hormone concentration leads to reproductive problems, including disturbed folliculogenesis, impaired ovulation and fertilization rates, miscarriage and pregnancy complications. The objective of the present study is to examine the consequences of chronic hypothyroidism, induced in adulthood, for the size of the ovarian follicle pool. In order to investigate this, adult female rats were provided eit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
(66 reference statements)
3
16
0
Order By: Relevance
“…A recent animal model of chronic hypothyroidism studied its effects on the growing follicle population. After rats were made hypothyroid through a 16-week low iodine diet, there was a significant decrease in the number of growing follicles (28). An in vitro study using rat ovarian cells showed that high doses of triiodothyronine (T3) induced an increase in follicle volume of 40% after 7 days in culture, while T3 decreased rates of apoptosis of granulosa cells, when they were cultured in medium deprived of serum, similar to the effects seen with FSH (29).…”
Section: Thyroid and Reproductive Physiologymentioning
confidence: 89%
“…A recent animal model of chronic hypothyroidism studied its effects on the growing follicle population. After rats were made hypothyroid through a 16-week low iodine diet, there was a significant decrease in the number of growing follicles (28). An in vitro study using rat ovarian cells showed that high doses of triiodothyronine (T3) induced an increase in follicle volume of 40% after 7 days in culture, while T3 decreased rates of apoptosis of granulosa cells, when they were cultured in medium deprived of serum, similar to the effects seen with FSH (29).…”
Section: Thyroid and Reproductive Physiologymentioning
confidence: 89%
“…Prolonged mild hypothyroidism may have a negative impact on the ovarian follicular reserve. [ 62 ] There is no specific treatment modality to suppress autoimmune destruction by modern medicine, therefore, seeking complementary and alternative therapy such as acupuncture in the early stage is of great significance for the treatment and fertility preservation in the child-bearing period female with HT.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the association of hypothyroidism with impairment of FOR has been examined in mice and rats after administration of PTU and low-iodine diet, respectively [ 75 , 76 ]. In both cases, the number of primordial, primary and preantral follicles was reduced whereas none significant change of atretic follicles was reported.…”
Section: Circulating Th/tsh Levels and Premature Ovarian Dysfunctimentioning
confidence: 99%
“…In both cases, the number of primordial, primary and preantral follicles was reduced whereas none significant change of atretic follicles was reported. Although none explanation was supplied, the data suggested that the numeric reduction of preantral and antral follicles was not due to their degeneration under hypothyroid condition [ 76 , 77 ]. Noteworthy, in a previous paper, the same authors reported an impairment of FSH and LH surge with a concomitant alteration of the antioxidant enzymes (e.g., catalase, SOD1, and NOS) in ovaries from hypothyroid rats [ 78 ].…”
Section: Circulating Th/tsh Levels and Premature Ovarian Dysfunctimentioning
confidence: 99%